Early stage hepatocellular carcinoma in the elderly: a SEER database analysis - Oweira, Hani; Mehrabi, Arianeb (Journal of geriatric oncology, 2017)
Background Scarce evidence exists regarding the management of elderly patients (≥70years) with hepatocellular carcinoma (HCC). This study assessed the presentation and outcomes of elderly patients with early stage HCC. Methods Patient with early stage HCC (T1/T2N0M0), ≥70years, diagnosed between 2004 and 2013 were identified from the SEER (Surveillance, Epidemiology, and End Results) database. Propensity score matching (for receipt of localized treatment) was performed considering baseline characteristics (age, gender, race, tumor (T) stage, tumor size, fibrosis score, alpha fetoprotein level and histological subtype). Results A total of 6693 patients were identified. The median age group was 75-80years, and 2457 patients received local treatment (either surgical or non-surgical treatment). Both before and after propensity score matching, cancer-specific and overall survival (P<0.0001 for all) were better in the local treatment group. When stratifying the overall survival according to age group (70-80years vs. >80years) in the post matching cohort, patients treated with local treatment have better overall survival than those not treated regardless of the age group (P<0.0001 for both groups). In multivariate analysis of the matched population: local treatment, normal AFP and age (70-80years) were associated with better overall survival (P<0.0001, P<0.0001, P=0.047; respectively). Conclusion: Within the known limitations of the current SEER analysis, it may be cautiously suggested that elderly patients with early HCC should be properly selected for potentially curative local therapies. Prospective confirmation of these results should be conducted.
Gesehen am 30.04.2018